Scope position is a determining factor for diagnostic performance of endoscopic ultrasound-guided fine-needle aspiration for mass lesions in the pancreatic head - Nam Hee Kim; Hong Joo Kim (Society of Gastrointestinal Intervention, 2023)
Background: This study aimed to identify the clinical and endoscopic factors that determined the diagnostic performance of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) for mass lesions in the pancreatic head. Methods: A total of 78 consecutive patients with suspected mass lesions in the pancreatic head detected by contrast-enhanced multi-detector-row computed tomography and/or magnetic resonance imaging, who underwent EUS-FNA for cytologic and/or histologic confirmation in our institution between June 2012 and April 2017 were enrolled in the current study. Results: The sensitivity, specificity, positive predictive value, negative predictive value, and diagnostic accuracy of EUS-FNA for mass lesions in the pancreatic head in our series was 61/69 (88.4%), 9/9 (100.0%), 61/61 (100.0%), 9/17 (52.9%), and 70/78 (89.7%), respectively. In univariate analyses, the clinical and endoscopic factors for determining the diagnostic performance of EUS-FNA were the echoendoscope position during needle puncture (long vs. short scope position) and the distance from the echoendoscope to the mass lesion (< 1 cm vs. ≥ 1 cm). In the multivariate logistic regression analysis, the echoendoscope position during needle puncture was the only independent and significant determining factor for the diagnostic performance of EUS-FNA for mass lesions in the pancreatic head. Conclusion: The echoendoscope position during needle puncture is a determining factor for the diagnostic performance of EUS-FNA for mass lesions in the pancreatic head.